Dwarf Mistletoes (Arceuthobium, Viscaceae) of North America: Classification Systems, Phylogenetic Relationships, and Taxonomic Characteristics - Shawn C. Kenaley; Robert L. Mathiasen (Plants)
Arceuthobium—the dwarf mistletoes—is a clearly defined genus of hemi-parasitic plants in the family Viscaceae. The genus occurs throughout much of the Northern Hemisphere; however, the greatest concentration of species and subspecies occurs within coniferous forests of western North America, where considerable research was executed in the mid-to-late 20th century to determine their geographic distributions, host specializations, and taxonomic boundaries. However, the last monograph of Arceuthobium presenting morphological, phenological, phylogenetic, and physiological information for N. American dwarf mistletoes was published in 1996, and since that time, no subsequent publications have presented taxonomic information for the present classification of N. American Arceuthobium. Thus, herein, we provide updated phylogenetic and taxonomic data for 44 taxa of Arceuthobium indigenous to N. America while simultaneously addressing knowledge gaps and suggesting future research to improve our understanding of these ecologically and economically important forest tree parasites. The present classification systems for and recent treatments of N. American Arceuthobium are also discussed.